2013
DOI: 10.1097/rhu.0b013e31829cde53
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Day Delay in Synovial Fluid Crystal Identification Did Not Hinder the Reliable Detection of Monosodium Urate and Calcium Pyrophosphate Crystals

Abstract: Although immediate workup for microbiology, including Gram stain and culture, is indispensable and well established, crystal analysis may at times not be immediately performed. Our study suggests that when crystal identification cannot be done immediately, it can be safely performed up to 3 days after arthrocentesis when SF is stored at 4°C or even at stable room temperature (20°C).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
(22 reference statements)
1
29
0
1
Order By: Relevance
“…Tausche et al assessed the detectability of MSU and CPP crystals in 75 SF samples over a period of 3 days and showed that the crystal counts nor pH appeared dependent on whether the samples were sent in native (plain, sterile tubes) or anticoagulated tubes with EDTA. Also, neither significant cell decay between day 0 and 3 was evident nor secondary formation of crystals in EDTA-treated samples was observed [17]. Another study on 100 SF samples showed that the white blood cell (WBC) counts, performed after preserving SF for 24 and 48 h in EDTA tubes at 4°C, were very close to the values obtained just after arthrocentesis [16].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Tausche et al assessed the detectability of MSU and CPP crystals in 75 SF samples over a period of 3 days and showed that the crystal counts nor pH appeared dependent on whether the samples were sent in native (plain, sterile tubes) or anticoagulated tubes with EDTA. Also, neither significant cell decay between day 0 and 3 was evident nor secondary formation of crystals in EDTA-treated samples was observed [17]. Another study on 100 SF samples showed that the white blood cell (WBC) counts, performed after preserving SF for 24 and 48 h in EDTA tubes at 4°C, were very close to the values obtained just after arthrocentesis [16].…”
Section: Discussionmentioning
confidence: 89%
“…As far as we could find, there were no more recent studies on the subject. Based on the limited available evidence, EDTA preservation for several days seems comparable with instantaneous performed polarized light microscopy [14,16,17]. Thirdly, we used a conventional laboratory centrifuge, in contrast to other studies which used cytocentrifuges [6,7,9,10,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, mucin clot test, joint aspirate Gram stain test, and (in patients with monoarthritis) monosodium urate and calcium pyrophosphate examination using polarized microscopy are also known to be useful. 7 Further, high-tech and costly culture antibiogram or polymerase chain reaction (PCR) tests are also helpful but costly tests. 8 Recently neutrophil-to-lymphocyte ratio (NLR) -the level of neutrophil reflecting the severity of inflammation and lymphocyte count increasing after physiological stress -has been gaining popularity, which was, along with other inflammatory markers, commonly accepted as an accurate marker of the inflammatory status.…”
Section: Evaluation Of Neutrophil-to-lymphocyte Ratio As a Marker Of mentioning
confidence: 99%